Local Government Strategies in Regional Economic Recovery in Small Medium Enterprises (SME) During the Covid-19 Pandemic - Abdurrahman Sang (International Journal of Education, Information Technology, and Others, 2022)
Bekasi is one of the cities affected by COVID-19 which is one of the highest in Indonesia and has an impact on all dimensions, be it social, political and economic. Then the need for a special strategy in economic recovery where the strategy will be used by human resources who handle it in the Cooperatives and SME Agency. This study uses a descriptive qualitative research method. Based on the results of the SWOT analysis, the strategic recommendation given is a Progressive Strategy where this situation is very profitable, because the strengths possessed can be utilized for existing opportunities. The results of this study indicate that the economic recovery of SME through the Bekasi City Cooperative and SME Service has not run optimally so that the resulting strategy can improve SME training in terms of digitizing business marketing, and strengthening regulations that support the enthusiasm of SME actors such as permits to open businesses, import export licensing and point of marketing location.